2009
DOI: 10.1590/s1676-06032009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of the blue shark (Prionace glauca) off the coast of Brazil

Abstract: Stomachs from 222 blue sharks collected along the Brazilian coast were analyzed - 116 from the northeastern region and 106 from the southern region. A total of 51 prey taxa were identified. The most important prey items in the southern region were Mysticeti whales, teleosteans, the gempylid Ruvettus pretiosus and the nomeid Arioma bondi. Cephalopods were more diverse, with dominance of vertical migrants Histioteuthis spp., Cranchiidae and the epipelagic octopus Ocythoe tuberculata. In the northeastern region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
1
11
0
4
Order By: Relevance
“…The P. glauca, in turn, feeds mainly on teleosts, and the squids should only constitute a complementary diet. This pattern confirms results obtained by Bornatowski & Schwingel (2008) and Vaske-Junior et al (2009). Notwithstanding this, a result based on the analyses of 68 stomachs of such sharks caught at oceanic waters off the southern Brazilian coast (Vaske-Junior & Rincón-Filho, 1998) indicate a diet to be mainly based on squids, represented most frequently by the batipelagic Chiroteuthis veranyi.…”
Section: Discussionsupporting
confidence: 89%
“…The P. glauca, in turn, feeds mainly on teleosts, and the squids should only constitute a complementary diet. This pattern confirms results obtained by Bornatowski & Schwingel (2008) and Vaske-Junior et al (2009). Notwithstanding this, a result based on the analyses of 68 stomachs of such sharks caught at oceanic waters off the southern Brazilian coast (Vaske-Junior & Rincón-Filho, 1998) indicate a diet to be mainly based on squids, represented most frequently by the batipelagic Chiroteuthis veranyi.…”
Section: Discussionsupporting
confidence: 89%
“…For blue sharks, such surface orientated 'curiosity' could result in a meal. Several studies have reported blue sharks consuming birds [20,21] and lumpsucker fish (Cyclopterus lumpus), a fish associated with rafting seaweed [22]. Support also exists for blue sharks profiting from increased densities of surface-dwelling prey at dawn.…”
Section: Discussionmentioning
confidence: 99%
“…Blue sharks are a dietary generalist, consuming a wide variety of prey (Vaske Junior et al 2009), coupled with euthophagous habits (Henderson et al 2001;Campana et al 2011). The species appears to hunt in deeper water in during daylight hours and in shallower surface waters during nighttime (Tricas, 1979;Henderson et al 2001;Campana et al 2011;Doyle et al 2015).…”
Section: Oral Papillae and Implications For Gustationmentioning
confidence: 99%